IMPLEMENTASI LESSON STUDY UNTUK PEMBELAJARAN BIOLOGI BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATERI JARINGAN HEWAN DI MADRASAH ALIYAH NEGERI 2 PAMEKASAN - Khoirun Nisak; Faizatun Naja; Rizal Hafiqi; Trisuci Susianti; Agus Hidayat (Journal of Education Partner, 2023)
Observations were made in class XI IPS 3 on animal tissue in biology subjects and showed less active learning results in class. Many factors influence learning engagement and achievement. Factors originating from outside the individual are teacher factors in implementing inappropriate learning models and learning environments, while internal student factors are the lack of interest and lack of students in learning biology. This is because the learning model used is monotonous (traditional) so it makes students bored. To overcome these weaknesses, educational innovations are needed that bring fun to teachers and students. This research is descriptive research through the application of lesson study. The lesson study used is a school-based lesson study with 3 stages of implementation, namely: Plan (planning), do (implementation), see (reflection). In this case, the learning planning stage includes the preparation stage in PTK according to learning activities, the implementation and observation stage in PTK, and the viewing stage, the reflection stage in PTK. The research results show that the results of student activity presented in Table 1 at the first meeting were 58% active and very active students. These results indicate that the number of active students is not too high. This refers to student activities in each field, it can be seen in Table 2 which shows 100% of students passed the visual activities which included reading their own dictation, LKS, students paying attention to the pictures given by the model teacher. Students pay attention to the pictures contained in the worksheet. 46% of students carry out oral activities, by asking questions, answering questions from friends or teachers and responding to statements during group discussions. During group discussions, 83% of students did listening activities, including listening to friends and teachers' explanations. 63% of students' writing includes writing assignments related to the material being studied. From the results of this research, the application of lesson study in learning tissue systems in animals can improve student learning outcomes in class XI IPS 3 MAN 2 Pamekasan.